If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 5 + -2cosx Solving 3 = 5 + -2cosx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2cosx' to each side of the equation. 3 + 2cosx = 5 + -2cosx + 2cosx Combine like terms: -2cosx + 2cosx = 0 3 + 2cosx = 5 + 0 3 + 2cosx = 5 Add '-3' to each side of the equation. 3 + -3 + 2cosx = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 2cosx = 5 + -3 2cosx = 5 + -3 Combine like terms: 5 + -3 = 2 2cosx = 2 Divide each side by '2osx'. c = o-1s-1x-1 Simplifying c = o-1s-1x-1
| 24-4=6-7x | | 28=v-469 | | -49+9x=41+3x | | (4x-10)-6x+8= | | 9+4y=1 | | 90=4n+50 | | 7d+4=5d+15 | | 10n=290 | | .5y+1=.125y | | -7x-20=48-3x | | 36x=2 | | 5s+4.62=t | | 77=5x-8 | | 4x-10-6x+8= | | 150m-75+47750=50500-175 | | Y-2+3y=5y+4 | | 1158+(X+97)+x= | | 1158+(X+97)+x=3815 | | -33+4x=42+x | | 16sin^2c-8=0 | | 6.2z+1.53=29.43 | | D=-0.3n+35-(0.2n+10) | | -5x-y=-18 | | 37.61+0.50x=c | | x^2-10x-51=0 | | -2+9x=43 | | 10x-111=98-x | | 10x-13=180 | | -81=19+10 | | 6=18m | | 2(2y-1)-2(y)=2 | | 4.6(5x-3y)-5.2(8x+y)= |